Novel unsteady state method of measuring permeability tested on fabric materials - Sitar, Anže (Strojniški vestnik, 2022)
The necessity of measuring permeability is encountered in number of applications and some of them have adequate measurement techniques available. However, in the fields of freeze drying, composite scaffolds, 3D printed materials, etc., the sample materials have unique shapes and sizes, which disables the use of standardized equipment. Hence, a novel method was developed to determine the permeability of a sample material by analyzing a high frequency unsteady state pressure measurement acquired during the permeation of a working fluid. The method is also suitable for in-line measurements due to the rapid acquisition and analysis. The developed method is novel, hence a comparison of the acquired results and the permeabilities measured with a standard device designed for measuring air permeability of fabric materials was made. Air was the permeating fluid in the novel unsteady state as well as in the referential steady state measurements. The measured permeabilities ranged from approximately 8 Da to 50 Da for the analyzed five fabric materials. The comparative analysis yielded an encouraging linear fit with a R2 = 0.98 by including only one unsteady state measurement of each fabric sample. In addition, the presented method was capable of detecting the difference in permeability of the freeze-dried 5 wt% and 12 wt% aqueous mannitol solutions, which exhibit different permeabilities due to the different porosities after the same process of lyophilization. The possibility of determining permeabilities of freeze-dried pharmaceuticals is essential for lyophilization process optimization.
Keywords: flow resistivity; freeze-dried pharmaceuticals; liofilizirani proizvodi; nestacionarna metoda merjenja; nova merilna metoda; novel measurement method; permeability; permeabilnost; prepustnost; tkanine; unsteady state measurements